2017
DOI: 10.1080/02673843.2017.1377089
|View full text |Cite
|
Sign up to set email alerts
|

Gender moderates the association between polyvictimization and suicidal ideation among adolescents in the United Arab Emirates

Abstract: The evidence about the impact of polyvictimization on suicidal ideation among adolescents in the Eastern Mediterranean region is limited. The purpose of this study was to explore the association between polyvictimization and suicidal ideation while considering the potential moderating effect of gender on that association among Emirati adolescents. Secondary data (N = 2520) from the Global School-based Student Health Survey were analyzed. Gender was found to be a significant effect modifier of the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
3
3
0
Order By: Relevance
“…Further, being male and having a close relationship with one or both parents were identified as significant protective factors for suicide risk in bivariate analyses, but the relationships were not significant in the adjusted model. This is consistent with previous studies that females have higher suicide risk (Itani et al, 2018; Vijayakumar et al, 2005) and social support from family lowers suicide risk (Holt & Espelage, 2005; Turner et al, 2013). Given the significant result of being male, future studies may investigate the associations between ACEs and suicide risk, stratified by sex, to better understand suicide risk by sex and possibly narrow down its intervention efforts to more specific population among Zambian youth.…”
Section: Discussionsupporting
confidence: 93%
“…Further, being male and having a close relationship with one or both parents were identified as significant protective factors for suicide risk in bivariate analyses, but the relationships were not significant in the adjusted model. This is consistent with previous studies that females have higher suicide risk (Itani et al, 2018; Vijayakumar et al, 2005) and social support from family lowers suicide risk (Holt & Espelage, 2005; Turner et al, 2013). Given the significant result of being male, future studies may investigate the associations between ACEs and suicide risk, stratified by sex, to better understand suicide risk by sex and possibly narrow down its intervention efforts to more specific population among Zambian youth.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we confirmed that poly-victimised adolescents were more prone to self-harm and attempted suicide than students who had experienced one type of maltreatment (Baldwin et al, 2018;Itani et al, 2017;Soler et al, 2013;Turner et al, 2012). Moreover, we found that this risk increases with the number of different maltreatment types adolescents were exposed to.…”
Section: Discussionsupporting
confidence: 80%
“…A meta‐analysis published in 2018 demonstrated that outcomes include neurobiological abnormalities, mental disorders, deficits in cognitive functioning, sexual aggression, risky sexual behaviour and many more (Carr et al, 2018). Additionally, various studies indicate that exposure to maltreatment, particularly poly‐victimisation, can lead to self‐directed violence such as self‐harming and suicidal behaviours (Baldwin et al, 2018; Itani et al, 2017; Soler et al, 2013; Turner et al, 2012). In the scientific literature, these potentially traumatic events that might have long‐term deleterious impacts on health and well‐being are referred to as adverse childhood experiences (ACEs) (Boullier & Blair, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicidality and deaths by suicide in the Arab World are likely to occur due to a variety of factors. For instance, younger women were found to be more likely to report thoughts of suicide, which is similar to studies from elsewhere in the World, which likewise find that women are likely to report attempts (Dardas et al, 2017 ; Han et al, 2015 ; Itani et al, 2018 ; Kessler et al, 2005 ; Kronfol, 2012 ; O’Loughlin & Sherwood, 2005 ). Past studies from the Arab World had also shown that women who have experienced suicidality are likely to be younger (Halabi et al, 2020 ; Khan & Reza, 1998 ).…”
Section: Discussionsupporting
confidence: 74%